Physical and Mental Health Assessment Among School Age Children in Islamic School, Medan - Tumanggor, Roxsana Devi; Nurbaiti; Siregar, Cholina Trisa (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Children are individuals under the age of 18 years with significant physical and mental growth and development. But, in fact, this growth and development cannot be achieved perfectly. Based on the survey results, several factors are the causes of the child's optimal growth and development, such as economic factors, the level of knowledge and education of the mother. If examined, this factor is closely related to family poverty factors. Not only that, the data related to children's mental health is also almost non-existent, so that children not only face problems related to physical problems, but also problems related to psychological disorders. Therefore, it takes an intervention that can be done on children in optimizing physical and mental health. In this case an approach is needed in the form of school-based intervention in organizing a program for examining the physical and mental health of children. Program implementation has been carried out at the Tahfidz Plus Khoiru Ummah School, at the kindergarten level (17 children) and elementary school (30 children, grade 1-5 elementary school) by coordinating with school teachers who are responsible for each class. The first action taken was a physical examination for all kindergarten and elementary school children. Based on the results of the physical examination, there is no abnormality on the child's health scale. Child health problems found only with flu and cough problems. To overcome this, children have been taught related to health promotion in an effort to prevent disease by demonstrating proper hand washing, proper toothbrushing, wound care and diarrhea. For a physical examination of mental health, screening is done by inviting children to talk about their daily lives during a physical examination while identifying other symptoms outside the instrument checklist. There are 2 instruments used in children's mental health screening, namely Early Childhood Screening Assessment which will be used for kindergarten children and instruments for Social, Academic & Emotional Behavior Risk Screener for elementary school children. Based on the results of temporary screening, there was only one elementary school child who needed further treatment and needed more accurate discussion with the class teacher at the next meeting.